Estudio de películas nanocompuestas a base de almidon de batata (Ipomoea batatas L.) - Gutiérrez, Marina; Di Gregorio, Vanina; Corbino, Graciela Beatriz (Facultad de Farmacia y Bioquímica, Universidad de Buenos Aires, 2022)
Poster